Effect of aggregate structure on fracture process in concrete using 2D lattice model (Archives of Mechanics - Test, 2007)
The 2D lattice model was used to analyse fracture processes in concrete at the meso–level. Concrete was described as a three–phase material (aggregate, interfacial transition zone and cement matrix). The calculations were carried out for concrete specimens subject mainly to uniaxial extension. The effect of the aggregate density was investigated. In addition, a deterministic size effect was studied. The advantages and disadvantages of the model were outlined.